ANALISIS LIKUIDITAS, SOLVABILITAS, DAN RENTABILITAS TERHADAP KINERJA KEUANGAN PADA KOPERASI KREDIT BAKTI HUSADA LUBUKLINGGAU - Ardayana Ardayana; Eri Triharyati; Agustinus Samosir (Jurnal AkunStie (JAS), 2021)
The purpose of this study was to determine the financial condition of the Bakti Husada Lubuklinggau Credit Cooperative in 2015-2019 using Liquidity, Solvency, and Profitability Analysis. The problem in this research is that there are fluctuations in the number of current assets, total assets, remaining operating results, and total debt. Data collection techniques by observation, documentation and interviews. The results of the research for liquidity analysis using the current ratio and cash ratio using the standard ratio measurement based on the regulation of the Minister of Cooperatives and SMEs of the Republic of Indonesia in 2006, shows that the Current Ratio Value from 2015-2019 is categorized as very unhealthy while the cash ratio value is categorized as healthy. Solvency analysis using Debt to Asset Ratio and Debt to Equity Ratio, for Debt to Asset Ratio in 2015, 2016, and 2017 is categorized as unhealthy while 2018 and 2019 are categorized as very unhealthy. The Debt to Equity Ratio in 2015 – 2019 is categorized as very unhealthy. Judging from the profitability ratio in terms of ROA and ROI, it can be stated, based on ROA and ROI. In 2015, 2016, 2017 and 2018 they were in the healthy category, while in 2019 they were in the fairly healthy category.